Microporous Carbon and Mesoporous Silica by Use of Twin Polymerization: An Integrated Experimental and Theoretical Approach to Precursor Reactivity. Issue 7 (22nd April 2014) - Kitschke, Philipp; Auer, Alexander A.; Löschner, Tina; Seifert, Andreas; Spange, Stefan; Rüffer, Tobias; Lang, Heinrich; Mehring, Michael
Abstract: Spirocyclic silicon alkoxides were synthesized by reaction of Si(OMe)4 with derivatives of salicylic alcohol and studied by in situ differential scanning calorimetry with regard to twin polymerization (TP). Both, thermally induced and proton‐assisted TP gave nanostructured hybrid materials composed of a phenolic resin and silica. Carbonization and subsequent treatment with HF(aq) resulted in microporous carbon, whereas oxidation in air provided mesoporous silica. DFT calculations were performed to obtain a more detailed insight into the first reaction steps of proton‐assisted TP and to support the hypothesis of a reactivity scale based on steric and electronic features of the silicon‐containing precursors (twin monomers). The calculated reaction barriers for the initial reaction steps of proton‐assisted TP are qualitatively in accordance with the Hammett constants of the substituents at the salicylate moiety. This result offers a simple method to predict the reactivity for twin monomers. Abstract : On the double : The reactivity of a series of silicon‐containing spirocyclic compounds towards both thermally induced and proton‐assisted twin polymerization has been examined. The properties of the as‐obtained hybrid materials and the porous materials formed after consecutive treatments have been studied (see figure). Density functional calculations and calorimetry support a reactivity scale based on the Hammett substituent constants of the compounds.